2013
DOI: 10.1111/dmcn.12326
|View full text |Cite
|
Sign up to set email alerts
|

The association between children's contact with people with disabilities and their attitudes towards disability: a systematic review

Abstract: ABBREVIATIONS CATCHChedoke-McMaster Attitudes Towards Children with Handicaps STROBE Strengthening the Reporting of Observational Studies in Epidemiology AIM The aim of this review was to systematically review and synthesize observational evidence of associations between children's naturally varying contact with people with disabilities and their attitudes towards disability.METHOD A comprehensive search was conducted across multiple databases. Studies were included if they measured children's contact with peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 48 publications
(94 reference statements)
5
50
0
3
Order By: Relevance
“…In related fields, preschool children's exposure to people with disabilities resulted in more positive attitudes toward them (Hazzard, 1983;MacMillan, Tarrant, Abraham, & Morris, 2014). Taken together, these studies suggest that exposing preschool children to people who stutter may improve their stuttering attitudes.…”
Section: Educational and Clinical Implicationsmentioning
confidence: 77%
“…In related fields, preschool children's exposure to people with disabilities resulted in more positive attitudes toward them (Hazzard, 1983;MacMillan, Tarrant, Abraham, & Morris, 2014). Taken together, these studies suggest that exposing preschool children to people who stutter may improve their stuttering attitudes.…”
Section: Educational and Clinical Implicationsmentioning
confidence: 77%
“…Although the CATCH is the most commonly implemented scale to test children's attitudes towards people with disabilities [11], it has been criticised for the lack of transparency regarding whether it should be treated as a unidimensional scale or as three separate subscales of affective attitudes, behavioural intentions and cognitive attitudes [14,24]. Before conducting the analysis for this study, scale dimensionality was explored and the CATCH was revised to create two separate unidimensional scales of affective attitudes and behavioural intentions which were used for the main analysis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond direct face-to-face contact, positive attitudes can be formed through knowledge that fellow ingroup members have a positive relationship with an outgroup member ("extended contact") [10]. In the context of specifically disability attitudes, a recent review found that children's direct contact with people with disabilities is associated with more positive attitudes [11]. However, most of the research cited in the review was of poor quality, limiting the conclusions that could be drawn; furthermore, potential mediators or moderators of the contact-attitude association were not explored.…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…Therefore, it has been recommended that research identify effective ways to promote more positive societal attitudes towards people with disabilities [3,4]. Attitudes are difficult to measure directly; thus, they are often measured using self-report rating scales [5].…”
mentioning
confidence: 99%